2022
DOI: 10.1186/s13046-022-02544-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CEBPA-DT promotes liver cancer metastasis through DDR2/β-catenin activation via interacting with hnRNPC

Abstract: Background Hepatocellular carcinoma (HCC) is the world’s third leading cause of cancer-related death; due to the fast growth and high prevalence of tumor recurrence, the prognosis of HCC patients remains dismal. Long non-coding RNA CEBPA-DT, a divergent transcript of the CCAAT Enhancer Binding Protein Alpha (CEBPA) gene, has been shown to participate in multiple tumor progression. However, no research has established its cancer-promoting mechanism in HCC yet. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Considering that lncRNAs typically regulate target genes through interactions with RBPs, 30 we further identified CHKB-DT-interacting proteins. RAP-MS assays showed that FUS was a binding partner of CHKB-DT, while lncRNA CHKB-DT was predicted containing several FUS-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that lncRNAs typically regulate target genes through interactions with RBPs, 30 we further identified CHKB-DT-interacting proteins. RAP-MS assays showed that FUS was a binding partner of CHKB-DT, while lncRNA CHKB-DT was predicted containing several FUS-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LncRNA CEBPA-DT is upregulated in human HCC tissues with distant metastasis after surgery and is closely associated with poorer prognosis in HCC patients. A mechanistic study showed that CEBPA-DT can bind to heteroribonucleoprotein C (hnRNPC), promote the cytoplasmic translocation of hnRNPC, enhance the interaction between hnRNPC and DDR2 mRNA, and then promote the expression of DDR2[ 27 ]. Moreover, Wang et al [ 28 ] indicated that the expression of LINC00665 is upregulated in gastric cancer tissues and is associated with poor prognosis in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To give a couple of examples, the lncRNA CEBPA-DT is upregulated in HCC with distant metastasis and is associated with poor prognosis. Cai et al demonstrated that CEBPA-DT induced the epithelial-mesenchymal transition (EMT) through the upregulation of Snail1 by promoting the nuclear translocation of β-catenin [20]. Similarly, the lncRNA FTO-IT1 is overexpressed in HCC, and it emerged as a glycolysis-associated lncRNA influencing the metabolic shift of cancer cells by increasing their glycolytic capacity and proliferation rate.…”
Section: Role Of Noncoding Rnas In Hepatocarcinogenesismentioning
confidence: 99%